Trojan Horse Protest at Pashayan/Stockman Dinner At Fresno Hilton Hotel - Watkins, Howard::::::::: (1982)
Protesters carrying signs; Pam Whalen and Mike Rhodes carrying large banner "Latin America Support Committee FRESNO"